Associations Between Early Onset of E-cigarette Use and Cigarette Smoking and Other Substance Use Among US Adolescents: A National Study - McCabe, Sean Esteban (Nicotine Tob Res, 2018)
INTRODUCTION: This study examines the associations between early onset of e-cigarette use and cigarette smoking and other substance use behaviors among US adolescents. METHODS: Data were collected via self-administered questionnaires from a nationally representative sample of 2299 US high school seniors attending public and private high schools during the spring of their senior year in 2015 as part of the Monitoring the Future study. RESULTS: A higher percentage of adolescents who began using e-cigarettes in ninth grade or earlier (early onset) were found to report current and lifetime cigarette smoking and other substance use relative to those individuals who never used e-cigarettes or those who began using e-cigarettes later in the 12th grade. Multivariate logistic regression analyses indicated that the adjusted odds of alcohol use, cigarette smoking, marijuana use, nonmedical prescription drug use, and other illicit drug use among early onset e-cigarette users were significantly greater than those for individuals never having used e-cigarettes (adjusted odds ratios [AORs] ranged 9.5–70.6, p < .001). While these associations were significant for both experimental and frequent e-cigarette users, the effects of early onset were stronger among frequent e-cigarette users. Similarly, the odds of these substance use behaviors (except alcohol) among early onset e-cigarette users were also significantly greater than the odds for later onset e-cigarette users (AORs ranged 2.8–4.1, p < .05). CONCLUSIONS: Early onset of e-cigarette use was significantly associated with increased odds of cigarette smoking and other substance use behaviors. E-cigarette use is often preceded by alcohol use, cigarette smoking, and marijuana use, suggesting that more long-term prospective studies are warranted. IMPLICATIONS: To date, no studies have examined the probability of cigarette smoking and other substance use behaviors as a function of age at onset of e-cigarette use. In the present study, early onset of e-cigarette use was significantly associated with increased odds of cigarette smoking and other substance use behaviors. The findings reinforce the importance of addressing a wide range of substances including alcohol, traditional cigarettes, and marijuana when developing early primary prevention efforts to reduce e-cigarette use among youth.